OPTIMALISASI PROSES PEMBELAJARAN UNTUK MENGURANGI KEBOSANAN SISWA MELALUI PEMBELAJARAN EFEKTIF - Nurul Wanitahara; Natasha Yuningsih Rinnisa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
Learning boredom is one of the problems often found in the teaching and learning process in schools. This condition can reduce students’ concentration, motivation, and participation during learning activities. Therefore, effective learning is needed to create a more active, interactive, and enjoyable classroom atmosphere. Effective learning not only focuses on delivering material, but also emphasizes students’ involvement in the learning process. This article aims to examine the importance of optimizing the learning process to reduce student boredom through effective learning approaches. The method used in this article is a literature study by reviewing various theories and previous research related to effective learning, student boredom, learning models, and the use of instructional media. The results of the study indicate that innovative learning models, varied teaching methods, and interactive learning media can increase students’ interest, motivation, and participation in learning activities. Thus, the implementation of effective learning is expected to create meaningful learning experiences and improve the quality of education.